Comparison of Simple Hill Climbing Algorithm and Stepest Ascent Hill Climbing Algorithm in The Game Order of Numbers - Narti Eka Putria (IJISTECH (International Journal of Information System and Technology), 2022)
The arrangement of a series of numbers is a game that is in great demand by various groups, this game is very useful for all circles because this game requires concentration and sharpening the brain power of the player, if this game follows the existing rules it will produce output in the form of a solution. Arrangement of numerical series is an implementation of the Searching method. The process of compiling a series of numbers has strong rules in order to obtain a solution. Problems In this study, we are looking for a comparison between the Simple Hill Climbing Algorithm and the Ascent Hill Climbing Algorithm which method is the fastest to find a solution. The final result of this research is an arrangement of numbers that is in accordance with the sequence by looking at the time and memory used to obtain the final solution.The final result of this study concluded that the Ascent Hill Climbing Algorithm is easier and faster to find a solution compared to the Simple Hill Climbing Algorithm